(3GdJejjR GdJShjbjs - (3dGf(B, (3TGSJhfs ((3GdQjGV(B:s (3GdeDJef ddJhRjY(B,s, 1998)
(3JLO aj gPG GdcJGH (B: (3GOGQI GdeQGLY GdJShjbjI , GdCecGfjGJ GdOGNdjI hfbGW GdVYa, HfjI GdYed, GdaQU heUOQ GdJZjQ , ENJjGQ GdESJQGJLjGJ GdefGSHI , EOGQI GdefTCJ GdLOjOIs
(3GdeQGLY U(B.314s
Keywords: (3EOGQI GdJShjbs